A6.2 Inducible Tertiary Lymphoid Structures and Autoimmunity in a Novel model of Sialoadenitis in Wild-Type Mice. (25th February 2013) - Lucchesi, D; Bombardieri, M; Barone, F; Nayar, S; Proctor, G; Buckley, CD; Pitzalis, C
Abstract : Introduction: Salivary glands of patients with Sjögren's syndrome (SS) develop ectopic lymphoid structures (ELS) characterised by B/T cell compartmentalisation, the formation of high endothelial venules (HEV), follicular dendritic cell networks (FDCs), functional B cell activation with expression of activation-induced cytidine deaminase (AID) as well as local differentiation of autoreactive plasma cells. The mechanisms triggering ELS formation, autoimmunity and exocrine dysfunction in SS are largely unknown. Here we present a novel model of inducible ectopic lymphoid tissue formation, breach of humoral self-tolerance and salivary hypofunction following delivery of a replication-deficient adenovirus-5 (AdV5) in submandibular glands of C57BL/6 mice through retrograde excretory duct cannulation. Materials and Methods: Luciferase- or LacZ-encoding Ad5 were delivered in C57BL/6 mice salivary glands (SG) through retrograde cannulation. SGs were collected at various time-points 1, 2 and 3 weeks post-cannulation (pc) and frozen sections were graded for infiltration and stained for T/B cell segregation, FDCs and HEV markers. Submandibular salivary flow was induced by pilocarpine stimulation and the amount of saliva measured. Expression of TLS-related genes was investigated by TaqMan-PCR. Anti-viral antibodies and autoantibodies were detected by IF and western blot. Results: In this model, inflammation rapidly and consistently evolves from diffuse infiltration towards the development of SS-like periductal lymphoid aggregates within 2 weeks from AdV delivery. These infiltrates progressively acquire ELS features and support functional GL7+/AID+ germinal centres. Formation of ELS is preceded by ectopic expression of lymphoid chemokines CXCL13, CCL21 and CCL19 as well as lymphotoxin-β and is associated with development of anti-nuclear antibodies in 75% of the mice. Finally, reduction in salivary flow was observed over 3 weeks post AdV infection consistent with exocrine gland dysfunction as a consequence of the inflammatory response. Conclusions: This novel model has the potential to unravel the cellular and molecular mechanisms regulating ELS formation and their role in exocrine dysfunction and autoimmunity in SS.